2-D WFS Approach Through Field Transformation—Application to Performance Prediction in Standard Antenna Simulators - Constant M. A. Niamien (IEEE, 2021)
This paper presents a 2-D wavefield synthesis approach directly implementable in standard antenna simulation software. The approach uses a field transformation matrix and two array sets to design vertically and horizontally polarized wavefields, implemented with thin electric dipoles for their simple geometry. The synthesized wavefields positively correlate with numerical methods (FIT, FEM) obtained from full-wave simulations over various array sets (size, number, polarization, frequency). Synthesizing 2-D isotropic wavefields in both polarizations under an error vector magnitude (EVM) equal to or smaller than −30 dB is demonstrated over the largest test zone radius of $λ $ /10 with just three dipoles located at a minimum distance of $5λ $ far from the phase center. Application to a test antenna (folded dipole) anticipates the received power and MEG directly inside the antenna simulator in receiving mode. This valuable design option, not handled by most antenna simulators, helps optimize the antenna with the propagation medium characteristics during the design stage.